daca x=3√5,calculeaza (x²+x-2)²-x²(x²+1)+3(x-1)²
popa:
va rog mult
Răspunsuri la întrebare
Răspuns de
2
x=3√5 => x²=9×5=45
x²+x-2 = 45+3√5-2 = 43+3√5
(x²+x-2)² = (43+3√5)² = 43² + 45 + 2×43×3√5 = 1894+258√5
x²(x²+1) = 45×46 = 2070
3(x-1)² = 3×(45+1-2×3√5) = 135+3-18√5 = 138-18√5
E=1894+258√5 - 2070 + 138 - 18√5 = 240√5 - 38
x²+x-2 = 45+3√5-2 = 43+3√5
(x²+x-2)² = (43+3√5)² = 43² + 45 + 2×43×3√5 = 1894+258√5
x²(x²+1) = 45×46 = 2070
3(x-1)² = 3×(45+1-2×3√5) = 135+3-18√5 = 138-18√5
E=1894+258√5 - 2070 + 138 - 18√5 = 240√5 - 38
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Fizică,
10 ani în urmă
Matematică,
10 ani în urmă